Cyberattacks on ships: a wicked problem approach. Issue 4 (21st November 2018) - Mileski, Joan; Clott, Christopher; Galvao, Cassia Bomer
Abstract : Purpose: The maritime industry is increasingly impacted by the Internet of things (IoT) through the automation of ships and port activities. This increased automation creates new security vulnerabilities for the maritime industry in cyberspace. Any obstruction in the global supply chain due to a cyberattack can cause catastrophic problems in the global economy. This paper aims to review automatic identification systems (AISs) aboard ships for cyber issues and weaknesses. Design/methodology/approach: The authors do so by comparing the results of two receiver systems of the AIS in the Port of Houston; the JAMSS system aboard the Space Station and the "Harborlights" system for traffic control in the Port. Findings: The authors find that inconsistent information is presented on the location of same ships at the same time in the Port. Upon further investigation with pilots, the authors find that these inconsistencies may be the result of the strength of power with which an AIS is transmitted. It appears the power may be reduced to the AIS in port but that it varies within port and varies by pilot operators. This practice may open the AIS system for tampering. Originality/value: Further, this inconsistency may require further policy regulation to properly address cyber information in a port.